(untitled) (Plant Tissue Culture and Biotechnology, 2018)
Increase in atmospheric CO2 ([CO2]) improves the efficiency of the unsaturated photosynthetic system of C3 plants, like rice, which leads to high crop productivity and increased biomass production. Planting geometry using lower than standard planting density has been shown to be an alternative pre-screening technique for phenotypic plasticity as a proxy of [CO2] responsiveness. More than 200 indigenous rice genotypes were tested for several traits, such as plant height, tiller number, panicle number, panicle dry weight, straw dry weight, total dry weight and harvest index. Their relative response for these phenotypic traits at low density planting versus normal density was determined to assess the plasticity of the genotypes. Ten genotypes were identified as significantly [CO2] responsive based on their higher panicle dry weight and panicle number. Even though it was observed that genotypes with higher days to maturity (DM) were more plastic, rice genotypes with low DM had a significantly higher relative response to harvest index, implying that rice with low DM may also be considered to be responsive to higher [CO2]. In order to associate phenotypic plasticity with the genotype, 23 SSR markers physically close to genes involved in CO2 metabolism were used to amplify selected responsive and non-responsive rice. Out of 3 alleles amplified using RM17, allele A was found to be significantly associated with genotypes with higher phenotypic plasticity whereas allele C was associated with genotypes with negligible response. The identified rice genotypes and the associated marker RM17 can therefore be tested further for breeding of superior rice responsive to higher [CO2] envisaged in a changing climatic scenario of the future. Plant Tissue Cult. & Biotech. 28(1): 109-124, 2018 (June)